Halophilic Bacteria Producing Protease from Salted Fish in Ponrang, Luwu Regency, South Sulawesi - Ramadhan, Andi Muhammad Faiz; Ardyati, Tri; Jatmiko, Yoga Dwi (The Journal of Experimental Life Science, 2023)
The need for protease enzymes for medical and industrial purposes. The need for proteases in the world reaches 65% of the total sales of enzymes, and in Indonesia can reach 2.500 tons every year, and 99% percent of the enzyme needs are still imported from abroad. Salted fish is one of the foods that contain a lot of protein, which is about 42% in 100 g of salted fish. It allows the presence of proteolytic bacteria that have halophilic properties in salted fish. This study aims to explore the presence of proteolytic bacteria with halophilic properties in salted fish. Proteolytic isolates were isolated using SMA media from salted fish from Ponrang District, Luwu Regency, South Sulawesi. A qualitative test was carried out by measuring the clear zone formed in Skim Milk Agar (SMA). From the isolation process, 51 isolates were obtained. However, after the screening, only 25 pure isolates were found that formed a clear zone, followed by a quantitative test to see which isolates had stable activity at incubation times of 24, 48, and 72 hours using Tryptic Soy Broth (TSB) media. The results obtained four superior isolates, P1A1K, P2B2PS, P3C6PS, and P3C6P, then continued to quantify halophilic bacteria properties by administering NaCl with 15% and 20% concentration into TSB media for 24 and 48 hours incubation. Two isolates with the highest protease activity were P3C6P isolates with the activity of 43.23 ± 7.11 U.mL-1 at 15% salt concentration and 42.83 ± 3.04 U.mL-1 at 20% salt concentration and P2B2PS isolates of 38.05 ± 4.05 U.mL-1 at 15% salt concentration and 38.15 ± 1.47 U.mL-1 at 20% salt concentration. The two isolates were then tested for pathogenicity on blood agar media. It was found that only P3C6P isolates did not have pathogenic properties, so P3C6P isolates were continued with catalase, oxidase, and gram staining tests, which showed negative catalase and oxidase results and were gram-positive, followed by identification based on sequences. 16S rDNA and phylogenetic tree construction where isolate P3C6P was identified as Bacillus cereus with a 100% similarity level to the WHX1 strain. Keywords: Enzyme, Protease, Proteolytic, Salted Fish, 16s-rDNA.